Identifikasi Penyelenggaraan Rekam Medis Elektronik pada Klinik Penyakit Dalam di RSUD Kembangan - Syahrul Dwi Ramadhani; Noor Yulia; Puteri Fannya; Dina Sonia (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
The rapid development of information technology has penetrated into various sectors of life, including in the health sector, which has also had an impact on the development of computer-based medical record systems. The purpose of this study was to determine the implementation of Electronic Medical Records at the Internal Medicine Clinic at Kembangan Hospital. The research method uses descriptive methods with qualitative analysis on 10 informants by means of observation and interviews which will provide an overview and see directly a situation when the use of electronic medical records is carried out. The results showed that the hospital already had an SOP for filling in electronic medical records, which was not implemented according to what the officers did. The use of Electronic Medical Records, especially in the Internal Medicine Polyclinic, has gone well. Constraints from 5M Factor, namely Man, there are still registration officers who are incomplete or incorrect in filling in patient identity data, PPA (Professional Caring Provider) is incomplete in filling in patient diagnoses, Internet network material is sometimes slow, and the server is sometimes down, user complaints include display is less efficient, when filling. It is suggested to the Medical Record Unit, IT team and hospital management to evaluate the SOP, revise and socialize it in order to reduce the human error factor. Kembangan Hospital needs to improve the appearance of SIMRS Khanza to make it more attractive so as to increase the enthusiasm of the officers in inputting medical record data at SIMRS. Kembangan Hospital should improve network quality in the hospital environment to improve the performance of SIMRS.